2019
DOI: 10.7717/peerj.7103
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of research on the trends in autophagy

Abstract: Background Autophagy is an important mechanism to maintain homeostasis in cells. It has been linked with ageing and many currently incurable diseases, including heart disease, cancer, myopathies, neurodegeneration, and diabetes. Autophagy research is very important for identifying better treatments. This study aimed to explore the hotspots of autophagy research published from different countries, organizations, and authors. Methods Between 1962 and 2018, articles published about autophagy were identified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…[1][2][3] thedensity visualization map of co-authorship analysis plotted in figure 2, points out the major researchers with their strong coauthorship linkages. [4][5] The major clusters involved in the research with co-authorship can be identified in figure 2. Table 1 makes it clear that the most productive author isChen Whavingthe highest average citations andthehighest number of citations.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] thedensity visualization map of co-authorship analysis plotted in figure 2, points out the major researchers with their strong coauthorship linkages. [4][5] The major clusters involved in the research with co-authorship can be identified in figure 2. Table 1 makes it clear that the most productive author isChen Whavingthe highest average citations andthehighest number of citations.…”
Section: Resultsmentioning
confidence: 99%
“…Bibliometric analysis also provides a reference for accurately reading the literature and for selecting research directions. It has been widely applied in many fields ( Hong et al, 2019 ; Mi et al, 2021 ), including hotspots in POCD and the hundred most cited articles in PND ( Chen et al, 2020 ; Mi et al, 2021 ); however, few bibliometric studies have been performed on POD. This study aimed to quantify the basic information of scholarly publications and identify the most impactful literature, trends, and hotspots, thereby providing a comprehensive overview of the current status of POD research.…”
Section: Introductionmentioning
confidence: 99%
“…Given the catabolic degradation function of autophagy, it is not surprising that dysregulation of autophagy has been associated with numerous human diseases, including cancers, neurodegenerative diseases, autoimmune disorders, and inflammatory diseases ( 25 , 26 ). A total of 18,881 autophagy-related articles were published before 2019 and relevant research has dramatically risen in the past decade ( 27 ). Among which, the relationship between autophagy and cancer is one of the research hotspots.…”
Section: Introductionmentioning
confidence: 99%